The FIFO experience: A Gladstone case study - Cameron, Roslyn; Lewis, J.; Pfeiffer, L. (National Institute of Labour Studies, 2014)
The aim of this article is to explore the historic and contemporary use of nonresident workers (NRWs) in the Gladstone region, how this has contributed to the region’s development, and the economic and social impacts of the use of Fly-in Fly-out (FIFO) employment practices. Gladstone, in Central Queensland, is at the front and centre of Australia’s evolving economic growth with some $45 billion of investment being delivered in the region. Recently, the construction of three coal seam gas and liquefied natural gas (CSG and LNG) projects on Curtis Island in Gladstone harbour has placed enormous pressure on the region in terms of unprecedented labour and housing demands. It has seen the extensive use of FIFO and Drive-in Drive-out (DIDO) workers. An exploratory qualitative approach framed by key concepts in the literature on resource dependence and socio-economic well-being and, in particular, the fly-over effects of utilising large-scale FIFO labour practices is used in this study. A case study research design has been utilised involving archival and documentary analysis, and a series of qualitative semi-structured interviews with community stakeholders. Recent research into the socio-economic impacts on regional resource-dependent regions across Australia points to a shift away from the ‘resource curse’ hypothesis (Lawrie et al. 2011, Tonts et al. 2012). We argue that the Gladstone story is unique and is differentiated from the atypical story of the company-built inland mining town, due to a number of contextual variables. Key issues from multiple perspectives are identified and recommendations for future research are made.